2004
DOI: 10.1038/sj.bjp.0705446
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetic study on the utilisation of 5‐methyltetrahydrofolate and folic acid in patients with coronary artery disease

Abstract: 1 Methylenetetrahydrofolate reductase (MTHFR) is a regulating enzyme in folate-dependant homocysteine remethylation, because it catalyses the reduction of 5,10 methylenetetrahydrofolate to 5-methyltetrahydrofolate (5-MTHF). 2 Subjects homozygous for the 677C-T mutation in the MTHFR enzyme suffer from an increased cardiovascular risk. It can be speculated that the direct administration of 5-MTHF instead of folic acid can facilitate the remethylation of homocysteine in methionine. 5 All pharmacokinetic parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 17 publications
(15 reference statements)
0
37
1
1
Order By: Relevance
“…T polymorphism negatively affects the folate and homocysteine response [39]. However, in a pharmacokinetic study, no significant difference in pharmacokinetic parameters was found between patients with TT genotype and patients with CC genotype [40]. Likewise, in the present study, no significant difference was observed in the pharmacokinetic parameters of subjects having CC and CT genotypes of MTHFR.…”
Section: Pharmacokinetics Of Folic Acidcontrasting
confidence: 46%
“…T polymorphism negatively affects the folate and homocysteine response [39]. However, in a pharmacokinetic study, no significant difference in pharmacokinetic parameters was found between patients with TT genotype and patients with CC genotype [40]. Likewise, in the present study, no significant difference was observed in the pharmacokinetic parameters of subjects having CC and CT genotypes of MTHFR.…”
Section: Pharmacokinetics Of Folic Acidcontrasting
confidence: 46%
“…In a recent study comparing a single daily oral dose of 5 mg folic acid versus 5 mg of 5-MTHF, the peak concentration of 5-MTHF was nearly sevenfold higher than folic acid [30]. The authors also detected high levels of the non-natural isomer 6[R] 5-MTHF that lasted over a prolonged period of time; however, the significance of this isomer is not known.…”
Section: Discussionmentioning
confidence: 98%
“…The pharmacokinetic profile of 5-MTHF results in a higher bioavailability of folic acid irrespective of the patient’s genotype [30]. In a recent study comparing a single daily oral dose of 5 mg folic acid versus 5 mg of 5-MTHF, the peak concentration of 5-MTHF was nearly sevenfold higher than folic acid [30].…”
Section: Discussionmentioning
confidence: 99%
“…However, the [6R]-isomer of the racemic mixture is presumed to be biologically inactive and therefore without nutritional significance. In addition, adverse effects of the [6R]-isomer on storage are under discussion (Mader et al, 1995;Willems et al, 2004). Thus, interventional trials with the racemic mixture of 5-MTHF as conducted by Fohr et al (2002), Litynski et al (2002), and Willems et al (2004) are not considered in this chapter.…”
Section: Studies With the Natural Folate Form [6s]-5-methyltetrayhdromentioning
confidence: 99%